Предмет: Алгебра,
автор: CosmoStar0
Представьте в виде многочлена
(х-2)в квадрате+4х=
(х-3)(х+3)+3х в квадрате
2х(х-3)-3(х+2)=
(7а+х)в квадрате
Ответы
Автор ответа:
0
(x−2)^2+4x = x^2−4x+4+4x=x^2+4;
(x−3)(x+3)+3x^2 = x^2+x3−3x−9+3x^2=4x^2−9;
2х (х-3)-3(х+2)=2x2−6x−3x−6=2x2−9x−6;
(7а+х)^2=49a2+14ax+x2
(x−3)(x+3)+3x^2 = x^2+x3−3x−9+3x^2=4x^2−9;
2х (х-3)-3(х+2)=2x2−6x−3x−6=2x2−9x−6;
(7а+х)^2=49a2+14ax+x2
Похожие вопросы
Предмет: Математика,
автор: danilochek00
Предмет: Русский язык,
автор: erasylkhamitov932
Предмет: Математика,
автор: fatimalip82
Предмет: География,
автор: nechaevaliza